Sleep, Psychosocial Functioning, and Device-Specific Adjustment in Patients with Implantable Cardioverter Defibrillators (ICDs). Issue 1 (2nd January 2016) - McCrae, Christina S.; Roth, Alicia J.; Ford, Jessica; Crew, Earl C.; Conti, Jamie B.; Berry, Richard B.; Sears, Samuel F.
Abstract : Rates of sleep disorders and associated adjustment were examined in patients with implantable cardioverter defibrillators (ICDs; n = 42; M age = 61.57, SD = 12.60). One night of ambulatory polysomnography, 14 days of sleep diaries, and questionnaires (mood, sleepiness, fatigue, device acceptance) were administered. Controlling for ischemia, MANCOVA examined adjustment by sleep diagnosis. Apnea was most common (28.6%), followed by Insomnia (16.7%) and Comorbid Insomnia/Apnea (11.9%). Patients with insomnia reported poorer mood, greater sleepiness, and lower device acceptance than good sleepers; they also demonstrated poorer mood and less ICD device acceptance than patients with sleep apnea. Patients with comorbid insomnia/apnea also exhibited poorer mood and less ICD device acceptance than good sleepers; however, comorbid patients did not significantly differ from insomnia or apnea patients on any measure. Those with disordered sleep (regardless of type) reported greater fatigue than good sleepers. Assessment (and treatment) of difficulties with sleep, mood, fatigue, and device acceptance may be important for the comprehensive clinical management of ICD patients. Further research appears warranted.